Sólidos geométricos: uma abordagem histórica, conceitual e aplicada sobre volumes - Santos, Robson Francisco dos (2023)
In this work, the concept of volume of the main geometric solids studied in high school is alluded to – the teaching modality for which it is intended. In this approach, priority was given to calculating the volume of the Prism, the Pyramid, the Cylinder, the Cone, and the Sphere, in two aspects: Cavalieri’s principle - a method very present in textbooks of the last stage of basic education and the use of the process of integration as an alternative method in the deduction of the volume formulas of the solids studied here. It is also versed on the application of the concept of volume addressed in some external evaluations–OBMEP and ENEM; in addition to portraying the historical importance of spatial geometry, its teaching and learning both in the students’ school life and in their social life. Considering that a field study was carried out showing the application of knowledge acquired in the classroom on the concept of volume, whether empirical or cognitive, and the impact of this learning on the decision-making of a citizen who aims to improve his production of inputs food products for cattle raising, without losing sight of the cost/benefit of this whole process.